2015
DOI: 10.1371/journal.pone.0129249
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Differentially Expressed Genes and Natural Antisense Transcripts in Sheep (Ovis aries) Skin with Different Wool Fiber Diameters by Digital Gene Expression Profiling

Abstract: Wool fiber diameter (WFD) is the most important economic trait of wool. However, the genes specifically controlling WFD remain elusive. In this study, the expression profiles of skin from two groups of Gansu Alpine merino sheep with different WFD (a super-fine wool group [FD = 18.0 ± 0.5 μm, n= 3] and a fine wool group [FD=23.0±0.5μm, n=3]) were analyzed using next-generation sequencing–based digital gene expression profiling. A total of 40 significant differentially expressed genes (DEGs) were detected, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 102 publications
0
19
1
1
Order By: Relevance
“…Recently, the NGS-based RNA-Seq approach has been widely employed for the identification and profiling of apoptosis-related genes in many species (Deng et al, 2014; Liu et al, 2015; Yue et al, 2015). In this study, using RNA-Seq technology, many DEGs involved in apoptosis regulation were identified and characterized at the different stages of spermatogenesis in P. sinensis .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the NGS-based RNA-Seq approach has been widely employed for the identification and profiling of apoptosis-related genes in many species (Deng et al, 2014; Liu et al, 2015; Yue et al, 2015). In this study, using RNA-Seq technology, many DEGs involved in apoptosis regulation were identified and characterized at the different stages of spermatogenesis in P. sinensis .…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise nature of the epidermal placode-inducing “first dermal message” remains poorly understood, several studies have suggested that HF initiation is an orchestrated interaction between mesenchymal and epithelial cells mediated through the secretion of stimulator and inhibitor signaling molecules, such as Wnt / β-catenin , EDA / EDAR / NF-κB , Noggin / Lef-1 , Shh , BMP-2 / 4 / 7 and FGF [ 9 , 14 ]. Recent studies looking beyond protein-coding genes have shown that non-coding RNA (ncRNA), such as microRNA(miRNA),natural antisense transcripts (NAT) and long non-coding RNA (lncRNA), can show higher specificity as biomarkers for some applications than protein coding genes [ 15 19 ]. Among these ncRNAs, lncRNAs are not only large in quantity but also play important roles in gene expression regulation in organisms [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The phenotypic mean of microsatellites was analyzed by the generalized linear model (GLM) of SAS (V6.12) software, and multiple comparisons between genotypes were performed using the least significant difference method (LSD) [26] .…”
Section: Methodsmentioning
confidence: 99%